Local‐Scale Advection of Sensible and Latent Heat During Snowmelt. Issue 19 (5th October 2017) - Harder, Phillip; Pomeroy, John W.; Helgason, Warren
Abstract: The breakup of snow cover into patches during snowmelt leads to a dynamic, heterogeneous land surface composed of melting snow, and wet and dry soil and plant surfaces. Energy exchange with the atmosphere is therefore complicated by horizontal gradients in surface temperature and humidity as snow surface temperature and humidity are regulated by the phase change of melting snow unlike snow‐free areas. Airflow across these surface transitions results in local‐scale advection of energy that has been documented as sensible heat during snowmelt, while latent heat advection has received scant attention. Herein, results are presented from an experiment measuring near‐surface profiles of air temperature and humidity across snow‐free to snow‐covered transitions that demonstrates that latent heat advection can be the same order of magnitude as sensible heat advection and is therefore an important source of snowmelt energy. Latent heat advection is conditional on an upwind source of water vapor from a wetted snow‐free surface. Plain Language Summary: During snowmelt snow cover becomes heterogeneous and lateral transfer of energy between bare and snow surfaces is an important but underrepresented component of the surface energy balance. To date, there have been no observations of latent heat advection which is the energy transfer associated with evaporation from ponded melt‐water and subsequent condensation upon downwind snow patches. This paper presents observations and a conceptual framework that is used to quantify this previously undocumented energy balance component. Latent heat advection can represent up to 33% of the snowmelt energy which has large implications for the snowmelt process. This work demonstrates that both sensible and latent heat advection processes need to be included in future snow modeling efforts in order to improve snowmelt predictions which have wide ranging water resource management implications. Key Points: Local‐scale latent heat advection is a previously undocumented source of energy for snowmelt Latent heat advection requires an upwind water vapor source Latent heat advection is an important snowmelt process in low relief areas where surface water storage during melt is likely